Statistical Summability through de la Vallée-Poussin Mean in Probabilistic Normed Spaces - Ayhan Esi (International Journal of Mathematics and Mathematical Sciences)
Two concepts—one of statistical convergence and the other of de la Vallée-Poussin mean—play an important role in recent research on summability theory. In this work we define a new type of summability methods and statistical completeness involving the ideas of de la Vallée-Poussin mean and statistical convergence in the framework of probabilistic normed spaces.